Developing Ideation Cards for Mixed Reality Game Design - Wetzel, Richard; Rodden, Tom; Benford, Steve (Transactions of the Digital Games Research Association, 2017)
Mixed reality games (MRGs) encompass a variety of gaming genres such as pervasive games, location-based games, and augmented reality games. They enrich the physical world with technology to create new and exciting possibilities for games – but at the same time introduce new challenges. In order to make the vast design space of MRGs easily accessible we have developed our Mixed Reality Game Cards. These are a deck of ideation cards that synthesize design knowledge about MRGs and enable collaborative design in a playful manner. In this paper, we describe the iterative development of the Mixed Reality Game Cards over the course of six studies. The final version of the cards constitutes a helpful tool for future designers of MRGs both for rapid idea generation as well as for more in-depth idea development. We achieve this by utilizing different types of domain-specific cards (Opportunities, Questions, Challenges) as well as promoting the inclusion of domain-extrinsic Theme cards and suggesting different rules for interacting with the cards.